The New Design Criteria For Steel Construction Concerning Occupational Health And Safety - Surya Hermawan; Gunawan Budi Wijaya (Universitas Lambung Mangkurat, 2019)
In Indonesia, the number of construction project increased, while the Occupational Health and Safety (OHS) is one of the main purposes of the construction project. However, the OHS is often neglected which is indicated by the high number of the work accident occurrences. To reduce the work risk, a safe design since the pre-construction stage which is often called prevention through design should be considered. In this research, the method was carried out by a literature study to collect theory and data from some sources, including journal, thesis and website which initiated by the National Institute of Occupational Safety and Health (NIOSH). Then, the research continued to field observation for collecting the references to help formulate the new design criteria. The outcome of this research demonstrates that the prevention step for the work accident should be done earlier in the project, which is in the design phase. By doing prevention, such as using the new design criteria with the OHS consideration or the prevention through design, could reduce the work accident risk that could occur in steel construction project. The new design criteria discussing 5 elements in steel structure including column, beam, rafter, endplate connection and angle plate connection by applying the elements of the OHS in advance.Keywords: new design criteria, steel construction, occupational health and safety